Strategi Place dalam Pemasaran Rumah Sakit di Indonesia; Systematic Review - Bandaso, Asriyanti; Kusumowardhan, Dyani; Tanjung, Herlin Putri; Marliani, Lili; Mokoginta, Megadianty (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2020)
Hospitals must have a good marketing plan to increase patient interest in using its services. Marketing mix is a marketing strategy consisting of product, price, place, promotion, people, process and physical evidence. The Place Strategy refers to the ease of consumers accessing services. For this reason, we want to know how the role of place strategy in hospital marketing mix in Indonesia. This systematic review uses the PRISMA method. Searching uses Google Scholar and Garuda Ristekdikti electronic databases. Inclusion criteria, research articles, published from 2010 to 2019, and carried out in Indonesia. The keywords are "Marketing Mix", Hospital, Place, and Indonesia. There are 15 articles that qualify for review. Six articles show place strategies affecting hospital marketing. Four articles do not affect. Three articles conclude as seven marketing mix influences each other. Two articles provide recommendations for place strategies for marketing. The effect of place strategy in hospital marketing depends on the external and internal conditions of the hospital. It is necessary to combine and coordinate the strategies contained in the marketing mix, not only place strategies are prioritized so that marketing can be done effectively.